Modeling Social Behavior: Mathematical and Agent-Based Models of Social Dynamics and Cultural Evolution - Bisin, Alberto (Journal of Economic Literature, 2024)
Alberto Bisin of New York University reviews “Modeling Social Behavior: Mathematical and Agent-Based Models of Social Dynamics and Cultural Evolution” by Paul E. Smaldino. The Econlit abstract of this book begins: “Explores ways of thinking about and studying complex social systems using mathematical and computational models, focusing on relatively simple dynamic models to aid in the study of social organisms and what they do together.”